The Metalloprotease Neprilysin Degrades and Inactivates Apelin Peptides. (5th July 2016) - McKinnie, Shaun M. K.; Fischer, Conrad; Tran, Kelvin M. H.; Wang, Wang; Mosquera, Fabricio; Oudit, Gavin Y.; Vederas, John C.
Abstract: The apelinergic system is a mammalian peptide hormone network with key physiological roles. Apelin isoforms and analogues are believed to be promising therapeutics for cardiovascular disease. Despite extensive studies on apelin‐13 degradation patterns, only one protease, angiotensin‐converting enzyme 2 (ACE2), had been implicated in its physiological regulation. Through use of a peptide‐based fluorescent probe, we identified the metalloprotease neprilysin (NEP, a target for Entresto used in treatment of heart failure) as an enzyme that cleaves apelin isoforms. In vitro NEP proteolysis generated fragments that lacked the ability to bind to the apelin receptor, thereby making NEP the first protease to fully inactivate apelin. The involvement of NEP in the apelinergic system contributes to the understanding of its role in cardiovascular physiology. Abstract : Illuminating cardiovascular physiology : Apelin is a potent mammalian peptide hormone with significant physiological roles but poorly understood regulation. A synthetic peptide‐based fluorescent probe aided the identification of metalloprotease neprilysin as a negative regulator of apelin action, thus shedding light on the role of neprilysin in cardiovascular health.